De’villa ventures : G-socks / Muhammad Syazwan Mohd Azi... [et al.] - Mohd Azi, Muhammad Syazwan; Mohamad Rozi, Muhammad Waliuddin Faiz; Khirulanuar, Muhammad Shahrul Haikal; Mohd Rahim, Muhammad Faiezzam; Marhalim, Aqilah Nur Hazirah (2019)
This strategic agreement shows a diagram of business portrayal, exercises and objectives inside three years anticipating business period Our mission is to sell a socks that can make customers feel comfort when wear it in a long time The customers that we target are kids, teenagers, and adult. Our product comes with various size from small to large.